Isolated Renal Mucormycosis in a Case of Bone Marrow Transplant with Diabetes Mellitus - Dr. Sanjay P. Dhangar (SP’z Series New Insights on Urology and Urological Research Part I, 2022)
Introduction: We present a first rare case of isolated renal mucormycosis in a diabetic bone marrow transplant patient. So far no case has been reported in the world literature. Mucormycosis is a rare opportunistic infection caused by the genera Rhizopus, Rhizomucor, Absidia and Mucor. Isolated renal mucormycosis is extremely rare. It is usually seen in immune-compromised patients and those with haematologic malignancies & diabetes mellitus. Materials and Methods: A 50 year old patient presented with complaints of fever for 1 month, left flank pain for 15 days, generalised weakness, inability to walk, amnesia & disorientation for 7 days. Physical examination revealed left flank tenderness, anaemia, pedal oedema. Blood, urine and radiological investigation were done. Results: Laboratory evaluation showed anaemia, leucopenia with neutropenia thrombocytopenia, hyponatremia, hyperkalemia, hyperglycemia. Serum creatinine was normal. Urine examination show 40-50pus cells, abundant RBCs, ketonuria. Urine culture showed significant growth of K. Pneumoniae, sensitive to colistin & polymyxin. Blood culture did not show any growth. Ultrasound suggested left pyelonephritis, no perinephric abscess/collection. CT suggested left kidney infarct due to renal artery thrombosis, with markedly bulky, swollen left kidney with complete loss of cortico-medullary differentiation, no perinephric collection and no enhancement of parenchyma on post-contrast study,. DTPA scan showed negligible function in left kidney. During left nephrectomy surgery kidney was grossly necrotic with renal vessel thrombosis. HPE revealed left kidney with extensive infarction and evidence of mucormycosis with renal vessel thrombosis. Postoperatively patient received Amphotericin B and recovered well. Conclusion: We present a rare case of an isolated renal Mucormycosis in a diabetic bone marrow transplant patient in which by doing intervention at proper time we could save the patient.